2019
DOI: 10.3390/su11185046
|View full text |Cite
|
Sign up to set email alerts
|

Cow Milk versus Plant-Based Milk Substitutes: A Comparison of Product Image and Motivational Structure of Consumption

Abstract: Cow milk is under increased scrutiny due to its environmental impact and ethical considerations concerning animal welfare. At the same time, a rising share of consumers is switching to plant-based milk substitutes (abbreviated “plant milk”). The objective of this study was (1) to analyze the product image of plant milk and cow milk and (2) to compare the motivational structure behind the consumption of both product categories. For this purpose, a quantitative survey with Austrian consumers was carried out to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
142
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 45 publications
5
142
0
6
Order By: Relevance
“…While grain-based milks, such as from rice, have been demonstrated to have a high glycaemic index due to enzymatic hydrolysis during production [99], making these products potentially unsuitable for diabetics. In previous studies, the lower energy and fat content relative to cow's milk have been found to be triggers for plant milk consumption [6,81]. Indeed, we found some beverages to have low approximate solids content, which likely translated to lower energy, but potentially at the cost of reduced satiety relative to cow's milk.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…While grain-based milks, such as from rice, have been demonstrated to have a high glycaemic index due to enzymatic hydrolysis during production [99], making these products potentially unsuitable for diabetics. In previous studies, the lower energy and fat content relative to cow's milk have been found to be triggers for plant milk consumption [6,81]. Indeed, we found some beverages to have low approximate solids content, which likely translated to lower energy, but potentially at the cost of reduced satiety relative to cow's milk.…”
Section: Discussionmentioning
confidence: 57%
“…Results of our dietary modelling highlighted that by substituting cow's milk with some plant-based beverages in these age groups, the intake of some bone-health promoting nutrients, including protein, calcium and zinc, could be reduced. This is a disconcerting discovery, as consumers reportedly perceive plant-based milk alternatives to be mineral-rich and good for bones [5,6,81]. The benefits derived from cow's milk are likely attributable to the complex interactions between nutrients that synergistically promote bone and muscle anabolism, rather than solely as a source of essential minerals in bone formation itself [82], for example, calcium and Vitamin D. During stages of growth, the accrual of bone density is closely correlated with muscle mass [83], and muscle contraction is involved in maintaining bone density throughout life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These nuts due to their unique nutritional properties are very much appreciated in vegan diets, gluten free diets and paleo diets [1]. Nut consumption and associated health benefits gained much interest in recent times and even considered as alternative to milk and meat [2,3]. Nuts are the part of traditional Mediterranean diet and now the nutrition research community advocates its consumption in a regular basis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative plant-based inputs for the production of milk analogues, including an analysis of their dietary and biological value, are explored in [26], but fenugreek seeds are not considered as a potential input material for making this group of products. Issues of forming nutrient properties of plant-based milk analogues are highlighted in [27], but literary evidence about developments of plant-based milk analogues using fenugreek seeds are not given. The chemical composition of fenugreek and some of its biologically valuable substances are described in [28].…”
Section: Discussionmentioning
confidence: 99%